REPORT OF THE INTERNATIONAL ASSOCIATION OF FIRE CHIEFS AD HOC COMMITTEE ON FIRE-SAFE CIGARETTES (Tufts Archival Research Center, 2007)
Report prepared by the International Association of Fire Chiefs (IAFC) for the Ad Hoc Committee on Fire Safe Cigarettes. Developed in order to address the issue of fire safe cigarettes and to determine whether or not federal standards for cigarettes should be set. Determines that there is too little knowledge regarding the subject to make a conclusive statement about the effectiveness of fire safe cigarettes, and thus, at this time, they believe that the IAFC should not recommend federal standards. Attached are the resumes of all members of the committee as well studies that were done to assess the effectiveness of fire safe cigarettes.